Experimental study on the effect of the riveting process on the bending resistance of beams composed of galvanized Q235 steel - Xue Jingya; Wu Qing; Chen Xiaomiao; Ma Shiliang; Wang Yunqing; Mo Jianbing; Yang Jianming (High Temperature Materials and Processes)
In this article, a hollow flange beam (ARHFB) composed of self-piercing rivet (SPR) and galvanized steel sheet was proposed, and the process parameters and mechanical properties of SPR connection technology for Q235 galvanized steel sheet were studied. Through the Taguchi method tests, the thickness of the joint section and the interlocking depth were measured. The tensile and shear tests were carried out, respectively, to obtain the corresponding quasi-static curves. In the four-point bending experiment of ARHFB, the effects of connection including welding, self-tapping screw, and SPR on the bending resistance of ARHFB were compared. The bearing capacity of ARHFB with self-tapping screws is significantly lower than that of welded ARHFB, and the 100 mm spacing SPR connection has strong substitutability for welding.